High Power RF Discharge Detection Technique Based on the In-Phase and Quadrature Signals - Monerris-Belda, Oscar; Marin, Raul Cervera; Jodar, Miguel Rodriguez; Diaz-Caballero, Elena; Guillen, Carlos Alcaide; Petit, John; Boria, Vicente E.; Gimeno, Benito; Raboso, David (IEEE transactions on microwave theory and techniques, 2021)
High power radio frequency (RF) breakdown testing is a subject of great relevance in the space industry, due to the increasing need of higher transmission power and smaller devices. This work presents a novel RF breakdown detection system, which monitors the same parameters as the microwave nulling system but with several advantages. Where microwave nulling-a de facto standard in RF breakdown testing-is narrowband and requires continuous tuning to keep its sensitivity, the proposed technique is broadband and maintains its performance for any RF signal. On top of that, defining the detection threshold is cumbersome due to the lack of an international standardized criterion. Small responses may appear in the detection system during the test and, sometimes, it is not possible to determine if these are an actual RF breakdown or random noise. This new detection system uses a larger analysis bandwidth, thus reducing the cases in which a small response is difficult to be classified. The proposed detection method represents a major step forward in high power testing as it runs without human intervention, warning the operator or decreasing the RF power automatically much faster than any human operator.